The experience of Arab international students in universities in the UK - Abdulazeez, Yousif; Reppa, Irene; Mok, Zi Hong (Journal of International Students, 2025)
Many UK universities are actively working to attract more international students, including those from Arab countries. Due to the differences in languages, religious beliefs, and social priorities between Arab and British societies, Arab students have faced various challenges here. This review examines the experiences of Arab students, focusing on their expectations, challenges, and interventions implemented by universities. Prior to enrolment, they anticipate gaining cutting-edge knowledge, improving English proficiency, career advancements, and a supportive academic environment. However, upon arrival, they encountered language barriers and financial strain, as well as cultural differences, accommodation and supervision difficulties, affecting their personal wellbeing. Despite these challenges, interventions such as financial aid, accommodation support, cultural events, and language initiatives have enhanced their experiences. Active supervision and mentoring further contribute to their study success. Ultimately, this review addresses the challenges and suggests the implementation of successful supportive measures to enable Arab students to thrive in the UK.